Musadoc 2004 - International Network for the Improvement of Banana and Plantain (2004)
The 7th edition of the MusaDoc CD-Rom. Updated versions of the INIBAP databases, MusaLIT - containing over 8526 bibliographic records and abstracts on Musa, BRIS - the database of banana researchers (almost 900 records) are available and a banana thesaurus including 3653 terms. All recent publications are also included in MusaDoc 2004 - Last issues of InfoMusa, the abstracts of the ”1st International Congress on Musa: Harnessing research to improve livelihoods”, the abstracts of”Banana Root System: Towards a better understanding for its productive management”, Reports of the latest MusaCO Steering Committee meetings, INIBAP factsheets, Musafrica and INIBAP 2003 annual report. The CD-Rom also provides an updated summary of INIBAP's activities.